Consumo e meio ambiente na modernidade: dimensões educacionais e tecnológicas - Chaves, Alessandra Aparecida Pereira (2019)
By identifying the discourses and factors that interposed in the composition of consumption patterns of modern society, we analyze modernity in a dimension that goes beyond the history and borders of nations. The world representations conveyed by the media and the school environment justify the thought renewal, the ways of living, the consumption and the historical and social constitution of the future. It was important therefore to make a survey of the role of technologies, education, culture, neuroscience and marketing techniques to verify the complexity of the topic. Research has been added on physical and virtual documents such as newspapers, magazines, books and rules. In view of the theoretical positions, the terms were taken in a broader sense, referring to the plurality of aspects and dimensions of human experiences. In addition, ideas about the nature of the research problem, its objectives and purpose are developed, justifying and explaining under what theoretical framework the subjects were treated. The methodology used to collect and treat the data was exploratory-descriptive, with application of questionnaires and observation of the activities developed with students of municipal schools in Curitiba city, Brazil. Two university extension courses with adults and activities with children were developed to open discussions on consumption and consumerism. The dissertation gave relevance to the role of education in disseminating interdisciplinary reflections on consumption in modernity, changes in habits, preservation and environmental conservation. However, it is necessary that the desire for transformations permeate the acts and surpass the barriers of work with recyclable material and school gardens in order to expand the dialogues with the curricular contents.